Tritium label in studying sorption of humic substances by carbon-based nanomaterials - Chernysheva, Maria; Badun, Gennadii (European Journal of Chemistry, 2011)
Sorption capacity of single-walled carbon nanotubes, detonated nanodiamonds and graphene to humic substances was studied by radiotracer method. Tritium labeled brown coal humic acids and fulvic acids separated from Suwannee River were used as sorbates. Adsorption isotherms were described by Langmuir equation. It was found that, for all tested carbon-based nanomaterials, adsorption of coal humic acids is higher than of river fulvic acids. Adsorption capacity of nanomaterials in attitude to humic substances was changed in the order, nanodiamonds < single-walled nanotubes < graphene. Composites of humic substances with carbon-based nanomaterials were subjected to dynamic light scattering analysis.